Stormy Misty's foal - Henry, Marguerite; Dennis, Wesley (New York : Scholastic Book Services, 1968)
A foal, born in the aftermath of a great storm, and her famous mother help raise money to repair the storm damage on Chincoteague Island and restore the herds of wild ponies on Assateague Island.
Keywords: Chincoteague pony -- Fiction; Horses -- Juvenile fiction; Ponies -- Fiction; Stormy (Horse) -- Fiction; Stormy (Horse) -- Juvenile fiction; Chincoteague Island (Va.) -- Fiction